Synthesis, structure, and phase composition of high-entropy ceramics (HfTiCN)-TiB2 - Evseev, Nikolay S. (Russian journal of inorganic chemistry)
The phase composition and structure of the composite ceramic material (HfTiCN)-TiB2 obtained from the high-entropy system Hf-Ti-C-N-B in the mode of conjugated self-propagating high-temperature synthesis (SHS, combustion) has been studied. Quantification using the Rietveld method has shown that the content of the HfTiCN phase in the combustion products is 40 wt %, and the content of the TiB2 phase is 60 wt %. It has been established that the structure of SHS materials consists of HfTiCN particles and agglomerates, which are distributed in the TiB2 matrix. The average particle size of TiB2 and HfTiCN is 6.1 and 3.3 mu m, respectively. A probable mechanism for the formation of a composite material (HfTiCN)-TiB2 in the mode of coupled self-propagating high-temperature synthesis of the Hf-Ti-C-N-B system is proposed. The results presented indicate the fundamental possibility of obtaining a composite ceramic material (HfTiCN)-TiB2 by the method of self-propagating high-temperature synthesis.